2018
DOI: 10.3390/w10050568
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Soil Particles during Secondary Soil Tillage along Contour Lines

Abstract: A high percentage of arable land and erosion risk on agricultural land are typical of current agriculture. While tillage erosion is a less frequently studied issue, it impacts vast areas of agricultural land. Not all relationships between cultivation equipment, the gradient of the plot and other factors have been known until now. Intensive soil tillage can be a crucial erosive factor mainly when the cultivation equipment moves in a fall line direction. Nevertheless, even when the equipment moves along contour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A 1:50,000 scale soil texture map based on data from a Systematic soil survey of agricultural soils in Czechoslovakia (Zádorová et al, 2019; was used as input for this conversion. The resulting k till values (Figure 3a) were confronted with empirical derived values on experimental plots (Hrabalíková et al, 2016;Novák & Hůla, 2018) and did not show any significant bias.…”
Section: Modelling Tillage Erosionmentioning
confidence: 91%
See 1 more Smart Citation
“…A 1:50,000 scale soil texture map based on data from a Systematic soil survey of agricultural soils in Czechoslovakia (Zádorová et al, 2019; was used as input for this conversion. The resulting k till values (Figure 3a) were confronted with empirical derived values on experimental plots (Hrabalíková et al, 2016;Novák & Hůla, 2018) and did not show any significant bias.…”
Section: Modelling Tillage Erosionmentioning
confidence: 91%
“…The tillage transport coefficient, a fundamental parameter, is difficult to obtain due to the time consuming and costly, extensive field measurements required. Very few empirical studies have been reported in Czechia (Hrabalíková et al, 2016;Novák & Hůla, 2018). Therefore, herein, we used the non-linear relationship developed by Van Oost et al (2006), based on a regression analysis of available data of k till .…”
Section: Modelling Tillage Erosionmentioning
confidence: 99%
“…Low‐intensity tillage includes strip‐till and no‐till practices, but the majority (∼95%) of the areas with low‐intensity tillage are farmed using no‐till practices (Azzari et al., 2019). Measurements indicate soil transport coefficients for no‐till are at least 2 orders of magnitude lower (<5 kg ⋅ m −1 ⋅ yr −1 ) than coefficients for conventional tillage (Mollinedo, 2008; Petr & Josef, 2018). For simplicity, we simulate soil transport for no‐till farming using a value of 6 kg ⋅ m −1 ⋅ yr −1 (tangent of slope) or 0.06 kg ⋅ m −1 ⋅ yr −1 ⋅ % −1 (percent slope), which corresponds to D LIT = 0.005 m 2 ⋅ yr −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the terrestrial soil FHMa11 group, the Crenarchaeota candidate division YNPFFA is also likely to be associated with pH; however, the highest abundance of both classes ). This occurs in soils as a result of the translocation of sand in soil layers due to changes in soil use (PETR;JOSEF, 2018). This process alters aggregate structure and porosity (REINERT; REICHERT, 2006), with a consequent reduction in O2 availability (STEFANOSKI et al, 2013).…”
Section: Discussionmentioning
confidence: 99%